Thermodynamic analysis and assessment of a novel integrated geothermal energy-based system for hydrogen production and storage - Yuksel, Yunus Emre; Ozturk, Murat; Dincer, Ibrahim (PERGAMON-ELSEVIER SCIENCE LTD, 2018)
In this paper, thermodynamic analysis and assessment of a novel geothermal energy based integrated system for power, hydrogen, oxygen, cooling, heat and hot water production are performed. This integrated process consists of (a) geothermal subsystem, (b) Kalina cycle, (c) single effect absorption cooling subsystem and (d) hydrogen generation and storage subsystems. The impacts of some design parameters, such as absorption chiller evaporator temperature, geothermal source temperature, turbine input pressure and pinch point temperature on the integrated system performance are investigated to achieve more efficient and more effective. Also, the impacts of reference temperature and geothermal water temperature on the integrated system performance are studied in detail. The energetic and exergetic efficiencies of the integrated system are then calculated as 42.59% and 48.24%, respectively. (C) 2017 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: Geothermal power; Energy; Thermodynamic assessment; Hydrogen production; Exergy; POWER; CELL; Chemistry; Electrochemistry; Energy & Fuels